Cosmologia e experiência em Portugal no século XVI - Pedro Campos Franke (Navigator)
This article aims to raise a few preliminary questions about the role of cosmological theories in the context of Sixteenth Century Portuguese maritime expansion. Chalenged by the adversities of open sea navigation and by the long distances to be sailed, the Portuguese have called upon astrological knowledge – until then related specially to medical diagnosis and prognosis – for developing the theoretical foundations of astronomic navigation. Still centuries away from the last downfall of divinatory Astrology’s scientifical status, the areas of thought today know as Astrology and Astronomy were then permeable to each other, and coexisted in publications destined to a large group of readers, such as the texts know as Chronografias or Reportórios dos tempos, written by renowned portuguese cosmographers and astrologers.